Byzantine emperors on stamped Late roman/earLy Byzantine amphoras - Diamanti, Charikleia (Rei Cretariae Romanae Fautorum Acta, 2012)
Byzantine emperors used their seals to authenticate the state documents and to secure their correspondence or even bags containing coins, the so called apokombia which were ceremonial gifts distributed by them. their own effigy was depicted on these gold (χρυσόβουλλo) or lead (μολυβδόβουλo) seals of theirs. From the 6th century also lead seals of kommerkiarioi, which were used on commercial packages as a license of circulation of the stamped commodities, depict the emperor in a way similar to that of the imperial seals or coins. again, the stamping of silver vessels fabricated in state workshops, sometimes with the bust of the emperor (the so called imperial series) appears in the 6th century until around 670.